2013
DOI: 10.11622/smedj.2013052
|View full text |Cite
|
Sign up to set email alerts
|

Greater palatine foramen – key to successful hemimaxillary anaesthesia: a morphometric study and report of a rare aberration

Abstract: MeThODs The GPF was studied in 100 dried, adult, unsexed skulls from the state of Maharashtra in western India.Measurements were made using a vernier calliper. ResUlTsThe mean distances of the GPF from the midline maxillary suture, incisive fossa, posterior palatal border and pterygoid hamulus were 14.49 mm, 35.50 mm, 3.40 mm and 11.78 mm, respectively. The foramen was opposite the third maxillary molar in 73.38% of skulls, and the direction in which the foramen opened into the oral cavity was found to be most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 15 publications
2
21
0
Order By: Relevance
“…However, the mean anteroposterior diameter of GPF among Lebanese sample was higher than in the present study. 15 In the present study, average distance to midline from GPF was found to be 14.35 ± 2.56 mm, which is similar to the other reported studies, 16,17 and lower than that reported by other studies. 8,18 On the contrary, other studies have measured distance to midline from GPF on both right and left sides and found side-related differences in GPF findings.…”
Section: Discussionsupporting
confidence: 87%
“…However, the mean anteroposterior diameter of GPF among Lebanese sample was higher than in the present study. 15 In the present study, average distance to midline from GPF was found to be 14.35 ± 2.56 mm, which is similar to the other reported studies, 16,17 and lower than that reported by other studies. 8,18 On the contrary, other studies have measured distance to midline from GPF on both right and left sides and found side-related differences in GPF findings.…”
Section: Discussionsupporting
confidence: 87%
“…Ikuta and coworkers found in a cone beam computed tomography study that the GPF was located in 92 of 100 cases in the third molar region and in an average distance of 7.9 mm from the alveolar ridge (Ikuta et al. ), whereas a study in Indian skulls observed the GPF to be in the third molar region in only 73% of the cases (Sharma & Garud ). Monnet‐Corti and coworkers, who measured the distance of the main branches of the GPA from the palatal gingival margin in 198 plaster models of periodontally healthy patients, found that the average distance from the gingival margin to the GPA ranged from approximately 12 mm in the canine area to roughly 14 mm at the second molar level (Monnet‐Corti et al.…”
Section: Anatomical Landmarksmentioning
confidence: 99%
“…The anterior (greater) palatine nerve supplies the main sensory innervation to the palate. It branches off the maxillary nerve and passes through the greater palatine canal (GPC) to surface on the hard palate from the greater palatine foramen (GPF), and continues anteriorly, ending just short of the front incisors (Sharma & Garud, ).…”
Section: Introductionmentioning
confidence: 99%